2018
DOI: 10.1002/14651858.cd012975
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for women with posterior compartment prolapse

Abstract: Transvaginal repair may be more effective than transanal repair for posterior wall prolapse in preventing recurrence of prolapse, in the light of both objective and subjective measures. However, data on adverse effects were scanty. Evidence was insufficient to permit any conclusions about the relative effectiveness or safety of other types of surgery. Evidence does not support the utilisation of any mesh or graft materials at the time of posterior vaginal repair. Withdrawal of some commercial transvaginal mesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 32 publications
2
68
3
3
Order By: Relevance
“…Due to different methods and outcomemeasure reporting, comparing the results between this study and the RCT results is challenging, as these Original Research GYNECOLOGY ajog.org randomized studies have evaluated the outcomes of a selected vaginal compartment repair with selected surgical methods. 11,21,22 Furthermore, as RCTs are designed to evaluate the efficacy of an intervention, they have lower heterogeneity, and due to exclusion and inclusion criteria (such as certain degree of prolapse in a specific compartment), the patients often have greater potential for improvement than in a more heterogeneous, real-world sample; therefore, the benefits observed in RCTs often are diluted. In reality, prolapse often involves multiple vaginal compartments and the surgical method is chosen based on clinical judgment.…”
Section: Results Of the Study In The Context Of Other Observationsmentioning
confidence: 99%
“…Due to different methods and outcomemeasure reporting, comparing the results between this study and the RCT results is challenging, as these Original Research GYNECOLOGY ajog.org randomized studies have evaluated the outcomes of a selected vaginal compartment repair with selected surgical methods. 11,21,22 Furthermore, as RCTs are designed to evaluate the efficacy of an intervention, they have lower heterogeneity, and due to exclusion and inclusion criteria (such as certain degree of prolapse in a specific compartment), the patients often have greater potential for improvement than in a more heterogeneous, real-world sample; therefore, the benefits observed in RCTs often are diluted. In reality, prolapse often involves multiple vaginal compartments and the surgical method is chosen based on clinical judgment.…”
Section: Results Of the Study In The Context Of Other Observationsmentioning
confidence: 99%
“…This is the first step toward development of a core outcome set based on Delphi surveys and consensus meetings for posterior vaginal wall prolapse interventions. When the prevalence of the considered clinical situation or treatment is low and when the variables are many, defining a priori the outcomes and the outcome measures is a crucial requirement . It has been suggested that questionnaires could be divided into groups of specific questions to measure one domain of outcome (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…High quality meta‐analyses are lacking due to trial heterogeneity . Controversy exists on the efficacy of the interventions due to this heterogeneity and variation in outcome measures utilized in different studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional compartmentalized single-specialty approach to PFD meant that patients with symptoms and pathology affecting the female reproductive organs, the lower urinary and/or the gastrointestinal tracts were seen only by a single specialist, whose expertise did not necessarily span all three domains. This has been associated with inferior outcomes, including incomplete resolution of symptoms and high failure rates after surgery 6,11. As a result, the National Institute for Health and Clinical Excellence (NICE) recommended multidisciplinary team (MDT) management of patients with PFD to standardize treatment and improve patient outcomes 12…”
Section: Introductionmentioning
confidence: 99%